The heir of Whitestone - Coulter, Catherine (John Scognamiglio Books : Kensington Publishing Corp., 2026)
"When Alex Ivanov was 12, someone tried to kill him. Now, 11 years later, they still want him dead. England, 1842. Queen Victoria reigns, Buckingham Palace is overrun with rats, and the streets of London are filled with intrigue. Alex Ivanov is a brilliant young innovator, designing cutting-edge train engines. But Alex has a secret--he isn't really Alex Ivanov. As a boy, he was pulled from the Thames, presumed drowned, with no memory of who he was. Rescued and raised by the formidable Ryder Sherbrooke, Alex has built a new life, but his past is catching up with him. Lady Camilla Rohman has problems of her own. Trapped by a scheming stepmother and a family determined to see her married off, she is as clever as she is desperate. When fate throws her into Alex's path, their connection is undeniable. But as their whirlwind romance turns into marriage, danger follows. On their honeymoon, a series of deadly attacks make one thing clear--someone wants Alex dead. As they race to uncover the truth, old enemies and long-buried secrets come to light, leading them to a shocking revelation that will change everything ..."--